Economic liberalisation and the mobility of minority groups: Evidence from Māori in New Zealand - Isabelle Sin; Steven Stillman (IZA Journal of Migration, 2016)
Between 1984 and 1993, New Zealand undertook comprehensive market-oriented economic reforms. In this paper, we use census data to examine how the internal mobility of Maori compares to that of Europeans in New Zealand in the period after these reforms. It is often suggested that Maori are less mobile than other ethnic groups because of attachment to particular geographical locations. If this were the case, Maori may have been disadvantaged in the post-reform period because they were more likely to be living in adversely affected areas and less likely to move to pursue better employment opportunities. In contrast to the anecdotal evidence, we find that Maori are more mobile on average than similar Europeans. However, Maori who live in areas with strong networks of their iwi are slightly less mobile than Europeans. The difference between Maori who live locally to their iwi and those who do not is even more pronounced when we consider responsiveness to local labour market shocks. Non-local Maori are considerably more responsive to changes in economic opportunities than are Europeans, whereas local Maori are almost entirely unresponsive.
Keywords: J61; J15; R23; 330; Mobility; Migration; New Zealand; Māori; Labour market areas